Speech text of International Congress on Engineering & Technology (ICET) / Prof. Datuk Dr. Shahrin Sahib @ Sahibuddin - Sahib @ Sahibuddin, Shahrin (2023)
Alhamdulillah, praise be to Allah S.W.T, for His grace and abundant blessings that have brought us together this afternoon for the closing of the remarkable International Congress on Engineering & Technology (ICET) 2023.